A Comparative Study on In-vitro Nitric oxide scavenging activity between Zonegran and Levetiracetram - Manish Babbu UG; Karthik V P (Journal of Global Pharma Technology, 2020)
Zonegran and Levetiracetram are two new range of anti-epileptics available in the market. Studies have been made earlier to demonstrate the antioxidant activity of the drugs Zonegran and Levetiracetam. Both have a good antioxidant property but there was not any comparative study for both the drugs. This study is to compare the anti-epileptic drugs Levetiracetam and Zonegran and demonstrate which drug has higher antioxidant property through Nitric Oxide radical scavenging activity.Methods: Nitric oxide scavenging activity was determined according to GriessIllosvoy reaction, with the help of Griess reagent. Ascorbic acid is used as positive control for the study. Conclusion: The study done suggests that both Zonegran and Levetiracetram possess antioxidant properties. At lower doses, Zonegran shows higher antioxidant potential over Levetiracetram and at higher doses, Levetiracetram shows slightly higher antioxidant property.